Predictive role of parenteral and enteral nutrition duration in parenteral nutrition-associated cholestasis among very preterm infants - Ma, Xiaolei; Zhou, Ying; Guo, Yanting; Ye, Li (Frontiers in Pediatrics, 2025)
BackgroundParenteral nutrition-associated cholestasis (PNAC) is common among very and extremely preterm infants (VPT). This study aims to investigate the relationship between the duration of parenteral nutrition (PN), enteral nutrition (EN), and the PN/EN ratio and the occurrence of PNAC in VPT, with the goal of providing a basis for the early identification of high-risk infants in clinical practice.MethodsA total of 230 VPT were retrospectively enrolled and divided into two groups based on the occurrence of PNAC. Baseline characteristics such as gestational age, sex, and birth weight, as well as clinical features, were compared between groups. Multivariable logistic regression was used to analyze the association between the duration of enteral nutrition (EN), parenteral nutrition (PN), and the development of PNAC. Interaction effects between PN, EN, the PN/EN ratio, and clinical variables were also explored. Restricted cubic spline (RCS) regression was employed to assess potential nonlinear relationships between PN, EN duration, PN/EN ratio, and PNAC. Predictive performance was evaluated using the area under the receiver operating characteristic curve (AUC).ResultsInfants in the PNAC group had significantly lower gestational age, birth weight, and Apgar scores compared to the non-PNAC group. In contrast, the incidence of premature rupture of membranes and mechanical ventilation was significantly higher. In VPT, longer PN duration, shorter EN duration, and a higher PN/EN ratio were significantly associated with increased risk of PNAC, showing linear or near-linear trends. ROC analysis indicated that the PN/EN ratio had better predictive performance for PNAC than either PN or EN duration alone. Interaction analysis revealed that the association between PN/EN and PNAC risk was stronger in infants with lower birth weight and lower 1-minute Apgar scores.ConclusionsLonger PN duration, shorter EN duration, and a higher PN/EN ratio are significant risk factors for PNAC in VPT. The PN/EN ratio demonstrated the best predictive accuracy. The association between PN/EN and PNAC was more pronounced in infants with lower birth weight and lower 1-minute Apgar scores.